In vivo analgesic, anti-inflammatory, sedative, muscle relaxant activities, and docking studies of 3',4',7,8-tetrahydroxy-3-methoxyflavone isolated from Pistacia chinensis - Abdur Rauf; Umer Rashid; Zuneera Akram; Anees Saeed; Naveed Muhammad; Najla Al Masoud; Taghrid S. Alomar; Saima Naz; Marcello Iriti (AboutScience Srl, 2024)
Background: Pistacia chinensis is extensively employed in traditional medicine. This study aimed to isolate and evaluate the therapeutic effects of 3'4'78-tetrahydroxy-3-methoxyflavone from P. chinensis crude extract. Materials and Methods: The study utilized column chromatography for isolation. The plant extract and its isolated compound were assessed for in vivo analgesic (hot plate model), anti-inflammatory (carrageenan-induced paw edema), sedative (open field model), and muscle relaxing properties (inclined plane and traction test). Results: In the thermal-induced analgesic model, a significant analgesic effect was observed for the extract (25, 50, and 100 mg/kg) and the isolated compound (2.5, 5, 10, and 15 mg/kg) at higher doses. The extract (100 mg/kg) significantly prolonged latency time (21.98 seconds) after 120 minutes of administration. The isolated compound elevated the latency time (20.03 seconds) after 30 minutes, remaining significant up to 120 minutes with a latency time of 24.11 seconds. The anti-inflammatory effect showed a reduction in inflammatory reactions by 50.23% (extract) and 67.09% (compound) after the fifth hour of treatment. Both samples demonstrated significant sedative effects, with the extract hindering movement by 54.11 lines crossed compared to the negative control (180.99 lines). The isolated compound reduced the number of lines crossed to 15.23±SEM compared to the negative control. Both samples were also significant muscle relaxants. Docking studies indicated that the compound's therapeutic effect is due to inhibiting COX and nociceptive pathways. Conclusion: The isolated compound from Pistacia chinensis exhibits significant analgesic, anti-inflammatory, sedative, and muscle relaxing properties, with potential therapeutic applications by inhibiting COX and nociceptive pathways.